The influence of booklet media on tuberculosis knowledge among airport workers: A pre-experimental study - Ovany, Riska; Alvionesa, Miana Chesaria; Delyka, Merry (School of Health Sciences Al-Ma'arif, 2026)
Background: Tuberculosis remains a major public health challenge in high-mobility occupational settings, where frequent interpersonal contact increases the risk of disease transmission. Limited knowledge regarding tuberculosis transmission, prevention, and early detection among airport workers may contribute to delayed health-seeking behavior and sustained transmission within transportation hubs. Objective: This study aimed to examine the influence of booklet-based health education on tuberculosis knowledge among airport workers. Methods: This study employed a quantitative pre-experimental one-group pretest–posttest design. The population consisted of 88 workers at the Tjilik Riwut Airport Health Quarantine Post, Palangka Raya, Indonesia. A sample of 47 respondents was selected using an accidental sampling technique based on inclusion criteria. Tuberculosis knowledge was measured using a structured questionnaire administered before and after the intervention. The intervention consisted of tuberculosis health education delivered through a printed booklet. Data normality was assessed using the Shapiro–Wilk test, and differences between pretest and posttest knowledge scores were analyzed using the Wilcoxon signed-rank test. Results: The findings demonstrated a significant increase in tuberculosis knowledge following the booklet-based intervention. The mean knowledge score increased from 77.72 before the intervention to 90.28 after the intervention, accompanied by a reduction in score variability. Statistical analysis indicated a significant difference between pre-intervention and post-intervention knowledge scores (p = 0.001). The proportion of respondents with high knowledge levels increased, while moderate and low knowledge categories decreased after the intervention. Conclusion: Booklet-based health education significantly improved tuberculosis knowledge among airport workers. The use of printed educational media proved to be an effective, practical, and sustainable approach for enhancing health knowledge in high-mobility occupational settings.